Efektivitas Problem Solving Training untuk Menurunkan Stres Perawatan pada Family Caregiver Pasien Paliatif - Pratitis, Nindia (Persona:Jurnal Psikologi Indonesia, 2016)
This research was aimed to evaluate effectiveness of problem solving training to reducecaregiving stress among family of palliative care patient. This research used quantitative approachwith pre-experimental method. This research was conducted on three family member of palliativecare patients At puskesmas in Surabaya. The researcher carried out caregiving stress scale andinterview as data collecting techniques. Data were analyzed by SPSS 18.0 for windows with PairedSample T-Test statistic technique. Result showed that problem solving training can reducecaregiving stress among family of palliative care patients. although in a small number ofsignificance (p>0.05). These results indicate that there are several factors that influence theseresults include the emergence of other issues in the intervention.Keywords : problem solving training, caregiving stress, family of palliative care patients